Patrones de consumo de los jóvenes hijos de emigrantes, que reciben remesas, en la parroquia rural Chiquintad - Merchán, Xavier (2015)
The great contemporary global changes have been marked by migratory waves and cultural exchanges, technological, scientific, etc .; the that has influenced decisively in the economy, in the sense and understanding of development, intensity and type of consumption, in shaping and integration family, and new societal relationships in both the places of departure and places of arrival. Families living and palpable migration, especially of their parents, waiting for the return of those who have migrated or longing for their soon meeting, they have undergone a transformation in how they see and feel the world. According to previous observations we can say that the physical absence of parents because of migration it is establishing types and inadequately addressed consumption levels in young children of those mothers and absent fathers. In fact, "there is speculation in the departments of vocational guidance of Colleges and Schools, the influence of remittances sent to the children of immigrants have changed their consumption patterns, behavior and interests "1 changing the way you relate to the institutions, families and the environment. For many, the impact is negative; very few consider positive phenomenon.